The Influence of Price and Product Quality on Customer Satisfaction at Giu Snack Store in Pontianak City - Indri Wella Apriyanti; Muhammad Ebuziyya Alif Ramadhan (SAINTIS Publishing, 2025)
This study aims to examine the influence of price and product quality on customer satisfaction at Giu Snack Store in Pontianak City. The research employed a quantitative associative approach, with primary data collected through questionnaires distributed to 100 respondents determined using the Rao Purba formula and the purposive sampling technique. Data were analyzed using multiple linear regression after all research instruments were confirmed to be valid, reliable, and met the classical assumption tests. The results reveal a strong relationship between price and product quality with customer satisfaction (R = 0.710), with a coefficient of determination of 50.4% (R² = 0.504), indicating that the model explains more than half of the variation in customer satisfaction. Simultaneously, both independent variables have a positive and significant effect on customer satisfaction, while partially, price and product quality each show a positive and significant influence. These findings emphasize that fair price perception and consistent product quality are key factors in enhancing customer satisfaction. Future studies are recommended to include additional variables such as service quality, promotion, and brand image, expand the sample size and coverage, and employ a longitudinal approach to achieve more comprehensive and in-depth results.